Prevalence and associate factors of low birth weight in North Indian babies: a rural based study - Kumar, Manoj; Verma, Ramesh; Khanna, Pardeep; Bhalla, Kapil; Kumar, Raj; Dhaka, Rohit; Chayal, Vinod (International Journal Of Community Medicine And Public Health, 2017)
Background: LBW is universally used as an indicator of health status and is an important subject of national concern and a focus of health policy. LBW is the strongest determinant of infant morbidity and mortality in India. Regional estimates of LBW include 28% in south Asia, 13% in sub-Saharan Africa and 9% in Latin America. Among regions, South Asia has the highest incidence of LBW; with one in four newborns has LBW. In 2011, Indian Statistical Institute reported nearly 20% of new born have LBW in India. DLHS-4 (2012-2013) in Haryana found that the prevalence of LBW was as 12.7%. The aims and objectives of study were to know the prevalence and its associated factors of low birth weight in rural area of Haryana. Methods: The beri block (Jhajjar) which is rural field practice of department of Community Medicine Pt B D Sharma PGIMS Rohtak (Haryana) India, has one CHC Dighal having 20 sub-centers. 10 sub-centers were selected by simple random sampling from these 20 sub-centres and 800 study subjects were enrolled from June 2015 to May 2016 from selected subcentres. Results: In present study, prevalence of LBW was 17%. The study found that sex of baby, type of family, socioeconomic status, educational status of mother, occupation of mother, anemia and intake of IFA had significantly impacted on LBW in India. Conclusions: Prevalence of LBW is decreased by health and nutrition education, iron and folic acid supplementation, effective management of complication.